(untitled) (Clinics, 2013)
OBJECTIVE: Prolonged warm ischemia time and increased intra-abdominal pressure caused by pneumoperitoneum during a laparoscopic donor nephrectomy could enhance renal ischemia reperfusion injury. For this reason, laparoscopic donor nephrectomy may be associated with a slower graft function recovery. However, an adequate protective response may balance the ischemia reperfusion damage. This study investigated whether laparoscopic donor nephrectomy modified the protective response of renal tissue during kidney transplantation. METHODS: Patients undergoing live renal transplantation were prospectively analyzed and divided into two groups based on the donor nephrectomy approach used: 1) the control group, recipients of open donor nephrectomy (n = 29), and 2) the study group, recipients of laparoscopic donor nephrectomy (n = 26). Graft biopsies were obtained at two time points: T-1 = after warm ischemia time and T+1 = 45 minutes after kidney reperfusion. The samples were analyzed by immunohistochemistry for the Bcl-2 and HO-1 proteins and by real-time polymerase chain reaction for the mRNA expression of Bcl-2, HO-1 and vascular endothelial growth factor. RESULTS: The area under the curve for creatinine and delayed graft function were similar in both the laparoscopic and open groups. There was no difference in the protective gene expression between the laparoscopic donor nephrectomy and open donor nephrectomy groups. The protein expression of HO-1 and Bcl-2 were similar between the open and laparoscopic groups. Furthermore, the gene expression of B-cell lymphoma 2 correlated with the warm ischemia time in the open group (p = 0.047) and that of vascular endothelial growth factor with the area under the curve for creatinine in the laparoscopic group (p = 0.01). CONCLUSION: The postoperative renal function and protective factor expression were similar between laparoscopic donor nephrectomy and open donor nephrectomy. These findings ensure laparoscopic donor nephrectomy utilization in renal transplantation.